Exploring the influence of living arrangements on mental health among adolescents during the COVID-19 pandemic: a cross-sectional study in China - Fufu Sun; Yanxin Wang; Wenqing Li; Minmin Li; Tong Hui; Wei Shi (BMC Public Health)
Abstract Background Although scholars have extensively explored the impact of parents on the mental health of children and adolescents during the COVID-19 pandemic, the role of living arrangements has not received sufficient attention. Furthermore, the previous studies do not investigate whether living with a father or a mother has differing impacts on the mental health of adolescents, nor does it explore potential differences between biological parents and step-parents in this regard. Study aims This study aims to explore the impact of various living arrangements during the COVID-19 pandemic on the mental health of adolescents, with a particular focus on parental presence and family structure. Methods This cross-sectional study, conducted between October and November 2020, involved over 20,000 participants. General linear regression and one-way ANOVA were used for data analysis. Results Significant differences in positive mood levels were observed among different family living arrangements. Those living with both biological parents exhibited the highest positive mood. Compared to living with a father, living with a mother was associated with higher positive mood. Significant differences were also found between living with biological parents and step-parents. Conclusion The findings underscore the nuanced relationship between living arrangements and mental health among adolescents. This study provides valuable insights into the role parents play in the mental health of young people during the COVID-19 pandemic.